Perceptions of HIV-AIDS and motivation for HIV testing among Balinese tourist village community - Damayanti, Ni Kadek Winda; Raya, Nyoman Agus Jagat; Nurhesti, Putu Oka Yuli; Antari, Gusti Ayu Ary (Universitas Muhammadiyah Semarang, 2024)
The right perception of HIV-AIDS by the community of tourist villages can lead to the motivation to identify their HIV status. A tourist village has zero case of HIV-AIDS will have a positive impact on the health conditions of the tourist village community and increase in tourist visits. This study aims to determine the correlation between HIV-AIDS perceptions and the motivation for HIV testing in the tourist village community of Sayan Ubud, Bali. Descriptive correlation design with a cross-sectional approach was used in this study. The sample size was 353 respondents who were taken by proportionate random sampling. Spearman rank correlation test was used for data analysis. The result showed a correlated HIV-AIDS perception and HIV testing motivation (p=0.000; r=0.611). A better perception of HIV-AIDS leads to increased HIV testing motivation in the community. This study can be used as basic data in the preventive programme of new HIV cases through HIV testing services. Thus, the Sayan Ubud tourist village community can identify their HIV status without any negative stigma.